Six-dimensional considerations of Einstein's connection for the first two classes. I. The recurrence relations in 6-g-UFT - Kyung Tae Chung; Gye Tak Yang; In Ho Hwang (International Journal of Mathematics and Mathematical Sciences)
Lower dimensional cases of Einstein's connection were already investigated by many authors for n=2,3,4,5. This paper is the first part of the following series of two papers, in which we obtain a surveyable tensorial representation of 6-dimensional Einstein's connection in terms of the unified field tensor, with main emphasis on the derivation of powerful and useful recurrence relations which hold in 6-dimensional Einstein's unified field theory (i.e., 6-g-UFT):